Answer:
CD = 6.3
Explanation:
triangles CFG and CDE are similar, so their side lengths are proportional
this means CD/CF = CE/CG
since we don't know CF, we need to first solve for CF in order to find CD
luckily, we know CD = CF + FD, and FD is given:
CD/CF = CE/CG -> (CF + FD) / (CF) = CE/CG
multiply both sides by CF to get CF + FD = CE * CF / CG
move the terms with CF to one side, and the constants to the other side:
CF - CF(CE/CG) = -FD
solve for CF:
CF(1-(CE/CG)) = -FD, CF = FD / ((CE/CG) - 1) = (1.8)/(((2.4+6)/(6)) - 1) = 4.5
Since CD = CF+FD, CD = 4.5 + 1.8 = 6.3